LIPASE AND PROTEASE LEVELS ON KOMBUCHA FERMENTATION - Endah Rita S. D. (Bioma : Jurnal Ilmiah Biologi, 2013)
Processed tea is fermented Kombucha Tea is known as "(Kombucha Tea). Kombucha tea is a functional food which occupies a position somewhere between conventional foods and drugs, so it can be used in the prevention of a disease of functional foods are foods that are designed specifically to take advantage of certain bioactive compounds that have a role in preventing disease.The enzyme is part of a protein that acts as a biocatalyst, accelerate the rate of biochemical reactions in the body. Therefore, the enzyme can be able to improve the health functions of the body with Kombucha.The purpose of this study (1) Knowing the production of lipase and protease in fermentation of Kombucha tea with many type, (2) Knowing the best kinds of tea for lipase and protease levels are optimal.The method used in this study is an experimental method to the design of Completely Randomized Design. This study consisted of four treatments, namely (A) + Kombucha colony of tea without sugar solution, (B) + Kombucha colony of black tea, (C) + Kombucha colony of green tea and (D) + Kombucha colony of fragrant tea (jasmine tea) with 3 replications. The parameters are count lipase and protease levels.Data analysis was performed with Analysis of Variance (ANOVA), followed by Duncan Multiple Test Distance (UJGD). ANOVA from lipase production in Kombucha fermentation of tea with significant variations, as well as protease levels is significant.The results showed that the type of tea as a fermentation medium had a significant influence (p <0.05) on levels of lipase and protease produced during the fermentation process and Kombucha tea as fermentation mediaKey words: Lipase, Protease, fermented Kombucha mushroom, tea variation